Profil Pengajaran Guru Matematika Sekolah Menengah Atas Terhadap Pengelolaan Kelas pada Materi Barisan dan Deret Aritmetika - Maisah Maisah; Yuhana Faradila Muzam Roudloh; Gabrielle Ezra Prayoga; Imam Rofiki (LP2M Universitas Ibrahimy, 2025)
Classroom management is a crucial skill that teachers must master in order to create a conducive learning environment, enabling them to maximize the quality of learning in the classroom. Therefore, the aim of this research is to describe the teaching profile of mathematics teachers in a senior high school on the topic of arithmetic sequences and series. This research can serve as a guide for teachers to become more creative in managing their classrooms. The research type used was descriptive with a qualitative approach. The research collecting methods included observation and interviews. Data analysis was carried out through data reduction, data presentation, and drawing conclusion. The results of this research show that even though Teacher-Centered Learning (TCL was used, it did not make students passive, as the teacher consistently encouraged students’ participation. Additionally, the teacher effectively manages the classroom by utilizing technology that encourages the students’ learning motivation.